Pengaruh Bauran Pemasaran Terhadap Keputusan Nasabah Memiliki Tabungan Britama Pada Kantor Cabang Pembantu Bank Rakyat Indonesia Slamet Riyadi Makassar - Ratih Suwanti; Salim Basalamah; Jeni Kamase (Doktor Ilmu Manajemen, Universitas Muslim Indonesia, 2021)
The results of this study indicate that based on the partial test Product and Place have a positive but insignificant effect while price, promotion, employees, physical evidence and processes have a positive and significant effect, while the results of the simultaneous test of products, prices, places, employees, physical evidence and processes have a positive and significant effect. simultaneous positive and insignificant effect on Customer Decisions.